SURVEI TINGKAT KEBUGARAN JASMANI SISWA BOARDING SCHOOL SMP BUDI MULIA TELUKJAMBE KARAWANG - Rahmawan, Aziz; Ma’mun, Saepul; Kusuma, Aria; Fauzi, Dira (Universitas Hamzanwadi, 2024)
The purpose of the study was to assess the level of physical fitness of boarding school students. A good level of physical fitness can support learning activities and student achievement. The method used was the survey method with the Indonesian student fitness test instrument. The research data were analyzed using descriptive statistics. The results of students (55.8%) had a moderate level of physical fitness, as many as 31.2% of students had a poor level of fitness, and 13% had a good level of fitness. The results of this study indicate that there are still students who have a poor level of physical fitness. This can be caused by several factors, such as lack of physical activity, unhealthy diet, and lack of rest. It is concluded that there is a need for programs to improve physical fitness for boarding school students. These programs can be in the form of regular sports activities, education about healthy eating patterns, and the provision of adequate sports facilities. By increasing the level of physical fitness of students, it is hoped that it can also improve learning activities and student achievement at school.